Relationship Between Mental Health and Job Satisfaction Among Employees in a Medical Center Department of Laboratory Medicine - Mo Siu-Mei Lee; Ming-Been Lee; Shih-Cheng Liao; Fu-Tien Chiang (Journal of the Formosan Medical Association, 2009)
Mental disorders associated with insomnia, depression and anxiety are common in the community and the workplace. Many studies have found a close link between mental health and job satisfaction. The present study investigated the prevalence of psychiatric morbidity and level of job satisfaction, as well as the relationship between psychological distress and job satisfaction and associated factors, among nonphysician employees of a laboratory medicine department at a university medical center. Methods: A cross-sectional descriptive and correlational study design was used. The employees were recruited and asked to complete a set of questionnaires, including a five-item Brief Symptom Rating Scale (BSRS-5) and a 40-item Job Satisfaction Questionnaire (JSQ-40). A total of 38 (26.21%) males and 107 (73.79%) females with a mean age of 40.80 ± 7.3 years completed the entire set of questionnaires. Results: The prevalence of psychiatric morbidity defined by the BSRS-5 was 34.33%, with insomnia ranking the highest (28.36%), followed by depression (25.37%), hostility (24.63%), anxiety (23.13%), and inferiority (20.15%). Job satisfaction global assessment scores on a scale of 0 to 100 indicated that most respondents were satisfied with their jobs. In general, subjects with more severe psychological distress reported lower levels of job satisfaction on five dimensions measured by the JSQ-40. Factors related to organizational communication were especially important in overall job satisfaction and severity of psychological distress. Conclusion: The prevalence of psychiatric morbidity in the workplace is high. The severity of psychological distress is negatively associated with job satisfaction. Early detection of psychiatric morbidity through self-administered screening questionnaires, as well as implementation of organizational mental-health promotion programs, is recommended to improve employees' mental health and job satisfaction.